2022
DOI: 10.1186/s42155-022-00296-0
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric arteriovenous fistula embolization with a vascular plug for upper gastrointestinal hemorrhage: a case report

Abstract: Background Superior mesenteric arteriovenous fistula is a rare vascular anomaly often presenting with sequelae of portal hypertension, heart failure, or mesenteric ischemia. This report describes a patient with a previously unidentified superior mesenteric arteriovenous fistula who presented with variceal bleeding, thought to be the leading cause of mortality associated with this condition. Although this patient was initially referred for a transjugular intrahepatic portosystemic shunt procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The primary etiologies of SMAVF are associated with traumatic or iatrogenic injury, and congenital lesions. 1,2 Although many patients remain asymptomatic after unrecognized injury to the superior mesenteric artery (SMA) for many years, most previous studies reported delayed presentation of persistent epigastric pain, vomiting and nausea, ascites, mesenteric ischemia, or bleeding. The incidence of SMAVF is 0.09%, with a mortality rate of 39%-77%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The primary etiologies of SMAVF are associated with traumatic or iatrogenic injury, and congenital lesions. 1,2 Although many patients remain asymptomatic after unrecognized injury to the superior mesenteric artery (SMA) for many years, most previous studies reported delayed presentation of persistent epigastric pain, vomiting and nausea, ascites, mesenteric ischemia, or bleeding. The incidence of SMAVF is 0.09%, with a mortality rate of 39%-77%.…”
mentioning
confidence: 99%
“…[5][6][7] Since the first case was reported by Nusselt in 1947, there have been several case reports of SMAVF, with no randomized controlled trials. [1][2][3][4][5][6][7] Surgical ligation of the fistula was once considered the most successful treatment for traumatic SMAVF. However, this approach is associated with risks, surgical trauma, and long hospital stays.…”
mentioning
confidence: 99%